SURVEILANS KESEHATAN MASYARAKAT PESISIR PULAU MAITARA (STUDI DI KECAMATAN TIDORE UTARA KOTA TIDORE KEPULAUAN) - Husen, Abd Hakim; Rahman, Ismail (NHM PRESS, 2023)
Coastal areas are transition areas between land and sea ecosystems. The majority of coastal communities are fishermen, a group of people who are prone to poverty because their work is greatly influenced by weather conditions and seasons. Another problem that often arises in coastal areas is in the field of public health because they are transitional areas that can control sanitation in all physical factors of the human environment which may cause things that are detrimental to the physical development of human health and survival. This research aims to explore public health problems that occur on Maitara Island, North Tidore District, Tidore Archipelago City as one of the coastal cities in Indonesia. This research uses a descriptive survey conducted through field observations by directly observing the conditions and health problems that exist in coastal communities on Maitara Island, North Tidore District, Tidore Islands City.